Characterization of a DmdEGFP reporter mouse as a tool to investigate dystrophin expression. Issue 1 (December 2016) - Petkova, Mina; Morales-Gonzales, Susanne; Relizani, Karima; Gill, Esther; Seifert, Franziska; Radke, Josefine; Stenzel, Werner; Garcia, Luis; Amthor, Helge; Schuelke, Markus
Abstract Background Dystrophin is a rod-shaped cytoplasmic protein that provides sarcolemmal stability as a structural link between the cytoskeleton and the extracellular matrix via the dystrophin-associated protein complex (DAPC). Mutations in the dystrophin-encodingDMD gene cause X-linked dystrophinopathies with variable phenotypes, the most severe being Duchenne muscular dystrophy (DMD) characterized by progressive muscle wasting and fibrosis. However, dystrophin deficiency does not only impair the function of skeletal and heart muscle but may also affect other organ systems such as the brain, eye, and gastrointestinal tract. The generation of a dystrophin reporter mouse would facilitate research into dystrophin muscular and extramuscular pathophysiology without the need for immunostaining. Results We generated aDmd EGFP reporter mouse through the in-frame insertion of theEGFP coding sequence behind the lastDmd exon 79, which is known to be expressed in all major dystrophin isoforms. We analyzed EGFP and dystrophin expression in various tissues and at the single muscle fiber level. Immunostaining of various members of the DAPC was done to confirm the correct subsarcolemmal location of dystrophin-binding partners. We found strong natural EGFP fluorescence at all expected sites of dystrophin expression in the skeletal and smooth muscle, heart, brain, and retina. EGFP fluorescence exactly colocalized with dystrophin immunostaining. In the skeletal muscle, dystrophin and other proteins of the DAPC were expressed at their correct sarcolemmal/subsarcolemmal localization. Skeletal muscle maintained normal tissue architecture, suggesting the correct function of the dystrophin-EGFP fusion protein. EGFP expression could be easily verified in isolated myofibers as well as in satellite cell-derived myotubes. Conclusions The novel dystrophin reporter mouse provides a valuable tool for direct visualization of dystrophin expression and will allow the study of dystrophin expression in vivo and in vitro in various tissues by live cell imaging.